Fenomena Mahasiswa Generasi Z Di Instagram (Studi Kualitatif Fenomenologi Mengenai Motif Di Balik Kosongnya Feed Instagram Pada Mahasiswa Ilmu Komunikasi, Universitas Dharma Andalas) - Fachry Akbar (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to understand the motives of Communication Science students at Dharma Andalas University for emptying their Instagram feeds. This phenomenon, known as "Grid Zero" or "No Posts Yet," occurs when studentschoose not to upload any content. Alfred Schutz's phenomenological theory is used to analyze students' subjective experiences in managing their digital identities.The research employs a qualitative method with a phenomenological approach, focusing on the meaning behind these experiences. Participants were selected using purposive sampling, involving 3-10 subjects meeting specific criteria. The findings reveal several key motives, such as maintaining privacy, avoiding social pressure to post appealing content, and prioritizing academic activities. These motives reflect students' efforts to manage their digital identities authentically and create a social media space free from public expectations.